PERCEIVED DIFFICULTIES STUDENTS ARE FACED WITH WHILE READING AND THE EFFECTS IT HAS IN THEIR ACADEMIC PERFORMANCE - DINESH KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Language is what distinguishes human societies from other types of civilizations; in these societies, language is considered as a tool for communication between people and helps preserve social cohesion. Language is what distinguishes human societies from other kinds of civilizations. As a direct consequence of this, educational authorities place a high priority on the teaching of Arabic to students. On the other hand, in recent years there has been a greater emphasis placed on the education of English speakers due to the fact that English is the language of both the contemporary world and the scientific community. Reading is a mentally taxing performance that, when combined with other linguistic abilities such as listening, speaking, and writing, forms a language system that is regarded as one of the most prominent and important language systems, and an individual is dependent on this language system to acquire language proficiency for use in educational settings and in everyday life. Reading is a mental challenge that, when combined with other linguistic abilities such as listening, speaking, and writing, forms a language system that is regarded as one of the most prominent and important language systems (Ruddell, 1992). There are a lot of different schools of thought on what the point of reading is and how it comes across to different people depending on who you ask